2006
DOI: 10.1007/s10751-006-9434-y
|View full text |Cite
|
Sign up to set email alerts
|

Mössbauer spectroscopic studies of Fe-20 wt.% Cr ball milled alloy

Abstract: Interesting differences were noticed in the alloying process during ball milling of Fe-10 wt.% Cr and Fe-20 wt.% Cr alloys by 57 Fe Mössbauer spectroscopic studies. In both cases, there is almost no diffusion of Fe in Cr or vice versa up to 20 h of milling time. As the powders are milled for another 20 h substantive changes occur in the Mössbauer spectra showing atomic level mixing. But the two compositions behave differently with respect to alloying. Fe-20 wt.% Cr sample does not differ much in the hyperfine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
0
2
1
2
Order By: Relevance
“…The observation of paramagnetic component and diffusion of iron into minority element is in contrast with our earlier work on the Fe-Cr ball milled samples [15,16], where we have observed predominantly magnetic components with very small contribution (less than 5%) of paramagnetic component. It was concluded that diffusion of Cr atoms into the Fe matrix was preferred over the diffusion of Fe in Cr.…”
Section: Mössbauer Spectroscopycontrasting
confidence: 99%
See 1 more Smart Citation
“…The observation of paramagnetic component and diffusion of iron into minority element is in contrast with our earlier work on the Fe-Cr ball milled samples [15,16], where we have observed predominantly magnetic components with very small contribution (less than 5%) of paramagnetic component. It was concluded that diffusion of Cr atoms into the Fe matrix was preferred over the diffusion of Fe in Cr.…”
Section: Mössbauer Spectroscopycontrasting
confidence: 99%
“…In the present paper we describe studies on these alloys using Mössbauer spectroscopy. It was found for the Fe-Cr systems with the help of Mössbauer spectroscopy that during the course of milling Cr preferentially diffuses in the Fe matrix but iron does not diffuse in the Cr lattice [15,16]. As a result, sextets of decreasing hyperfine field (B hf ) value evolved with milling time but no significant paramagnetic component was created.…”
mentioning
confidence: 99%
“…There is a great body of papers relevant to the matter in which the Mössbauer spectroscopy was used as a research tool e.g. [148][149][150][151][152][153][154][155][156][157][158][159][160][161][162]. MS being sensitive to local arrangements of atoms permits following the alloying process versus milling time.…”
Section: Mechanical Alloyingmentioning
confidence: 99%
“…Одним из способов улучшения физико-механических свойств материала является его получение в наноструктурированном состоянии (размер зерен менее 100 nm). Существует много работ, касающихся получения нанокристаллических сплавов Fe−Cr с использованием механического сплавления (МС) [2][3][4][5][6][7][8][9]. Здесь важным вопросом является изучение механизмов деформационного атомного перемешивания.…”
Section: Introductionunclassified
“…Здесь важным вопросом является изучение механизмов деформационного атомного перемешивания. Так, в [9] для порошковых смесей Fe−Cr, содержащих до 20 at.% Cr, показано, что процесс МС происходит за счет диффузии Cr в Fe. МС более богатых хромом смесей (до 48 at.% Cr) изучалось в работах [10][11][12][13], в которых было показано изменение механизма МС при концентрации хрома в исходной смеси более 30 at.%.…”
Section: Introductionunclassified